The Effect of Bladder Meridian Acupuncture Therapy on Pain Changes in Patients with Low Back Pain at the Dr. Tan & Remanlay Institute - Henry Remanlay; Hari Iskandar Kang (Green Publisher Indonesia, 2025)
Low back pain affects 60–80% of the population and significantly impacts quality of life, with prevalence increasing with age. Common causes include poor posture, injury, and degenerative conditions. Conventional treatments often prove inadequate, prompting exploration of alternative approaches such as acupuncture from traditional Chinese medicine. Bladder meridian acupuncture therapy focuses on stimulating specific points related to the nervous system and has demonstrated effectiveness in pain relief through endorphin release and inhibition of pain pathways. This study aimed to explore the effectiveness of acupuncture in managing low back pain at Dr. Tan & Remanlay Institute by analysing data on changes in pain before and after intervention, to enrich the acupuncture approach in pain management. This study employed a quasi-experimental design with a pretest-posttest approach to evaluate the effects of bladder meridian acupuncture therapy on low back pain. The study aimed to assess pain reduction in 22 patients at Dr. Tan & Remanlay Institute who met the inclusion and exclusion criteria. Pre- and post-intervention data were collected using a 0–10 pain scale. The variables studied were pain level as the dependent variable and acupuncture as the independent variable. Analysis was conducted descriptively and inferentially using the Wilcoxon two-sample test, yielding a significant result (Sig. (2-tailed) = 0.001). The study confirms that bladder meridian acupuncture represents an effective, non-invasive therapeutic option for managing low back pain, offering valuable insights for integrating traditional and modern medical approaches in comprehensive pain management protocols.